Acoustic Silencer for a Dedicated Frequency - BRAŃSKI, Adam; PRĘDKA-MASŁYK, Edyta (Archives of Acoustics, 2025)
Acoustic resonators are useful for damping low frequencies. In cylindrical silencers (mufflers), the implementation of the resonance concept consists in selecting such a length of the expansion chamber (EC) that a wave of opposite phase is created in it, and with this opposite phase the incident wave is damped. Based on the plane wave theory (1D) and simple analytical calculations, it is possible to approximately determine the shortest length of the EC for a selected frequency; such a chamber represents the simplest silencer. Its efficiency is measured by the transmission loss (TL) value; increasing the TL value indicates that the silencer efficiency increases as well. The efficiency was improved in two ways: first, in single EC, by adding inlet, outlet, or both horizontal extensions, and second, by adding another EC. In the first case, the influence of the length of the horizontal extensions on TL was analyzed. In the second study, another dedicated EC was added, and the influence of the width and orifice diameter of the transverse partition on TL was analyzed. All analytical results were confirmed experimentally. The results indicate that, first of all, a simple silencer (single EC) is found to damp a dedicated frequency. In addition, simple changes in the structure of such a silencer significantly increase its efficiency.